2020
DOI: 10.3390/su12135440
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Formation Mechanism of China-ASEAN Tourism Cooperation

Abstract: Tourism cooperation is an essential element for tourism development in China-ASEAN countries and has made a significant economic contribution to destinations. This study investigates the structure of tourism cooperation in China-ASEAN relations and identifies a set of factors that affect tourism cooperation from a network perspective. By employing social network analysis, the results indicate that the scale of cooperation is small, and the efficiency is not high, although the restrictions on cooperatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 111 publications
2
11
0
Order By: Relevance
“…The analysis of tourism cooperation in this study shows that the interpretation of individualism, essentialism, and atomism has shifted to a better understanding of relations, backgrounds, and systems [16]. Previously, scholars have examined the preconditions and policy framework of tourism cooperation in some specific regions [1,4,7,9,42], but there are few in-depth studies on tourism cooperation among cities in the Yangtze River Delta region of China. The present study intends to help fill this research gap by analyzing tourism cooperation from a supply and demand perspective through network analysis of official news released by the Chinese government and quotations for tour routes published by travel agencies.…”
Section: Conclusion and Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The analysis of tourism cooperation in this study shows that the interpretation of individualism, essentialism, and atomism has shifted to a better understanding of relations, backgrounds, and systems [16]. Previously, scholars have examined the preconditions and policy framework of tourism cooperation in some specific regions [1,4,7,9,42], but there are few in-depth studies on tourism cooperation among cities in the Yangtze River Delta region of China. The present study intends to help fill this research gap by analyzing tourism cooperation from a supply and demand perspective through network analysis of official news released by the Chinese government and quotations for tour routes published by travel agencies.…”
Section: Conclusion and Discussionmentioning
confidence: 88%
“…In many countries, tourism may be more important than other economic sectors [6]. The development of tourism in China has entered the stage of regional competition and cooperation to maximize the tourist potential of scenic spots, tourist routes, and cities, and it has become increasingly common to seek regional cooperation to promote the sustainable development of tourism [7][8][9]. Scholars have studied the concept definition, theoretical basis [10,11], influencing factors and dynamic mechanisms [12], cooperation models, spatial organization [13], evaluated cooperation potential [14], cooperation evolution [15], and other aspects of regional tourism cooperation.…”
Section: Introductionmentioning
confidence: 99%
“…Tourist villages also can develop when the youth attend to the hospitality. Promoting the convenience of traveling for visitors is important as part of a tourism destination development strategy (Yin, Bi and Ji, 2020;Bonilla-Quijada, Tugores-Ques and Arriaga, 2021). Therefore, the youth work to increase competitiveness in managing tourist destinations requires a development strategy.…”
Section: Discussionmentioning
confidence: 99%
“…Li et al classified the various influencing factors of regional tourism cooperation into exogenous, endogenous, and random factors, mainly including economic, political, sociocultural, legal, demographic, and geospatial factors [27]. Yin et al identified a set of factors that affect tourism cooperation in China-ASEAN including differences in political system, governance, and income [28]. In addition to the abovementioned factors influencing cooperation between tourism destinations from the perspective of supply (including governments and enterprises), some scholars have also analyzed factors influencing cooperation between tourism destinations from the perspective of demand [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%